A darkness visible - Murphy, Seamus 1959- (Saqi Books, 2008)
From 1994 to 2006, Seamus Murphy photographed the effects of the Taliban regime, the tumultuous years of civil war, and the historical elections following the fall of the Taliban. Alongside scenes of war and politics, his magnificent photographs capture intimate images of domesticity, work, and leisure